INFLUENCE OF THE VAGINAL SIMULATOR ON THE QUALITY OF LIFE IN PATIENTS WITH PELVIC ORGAN PROLAPSE - Савельева, Ирина Вячеславовна; Ющенко, Марина Анатольевна; Черных, Наталья Степановна (Mother and Baby in Kuzbass, 2022)
Retrospective case-control study was conducted in 42 women with grade 1 pelvic prolapse in the early transition period. Compared with the Kegel exercise, the mechanical vaginal trainer more often reduced the clinical manifestations of prolapse and led to an improvement in most Pelvic floor impact questionnaire 7 quality of life measures.